2018
DOI: 10.1016/j.heliyon.2018.e01009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic investigation, molecular docking and DFT studies of novel (2Z,4Z)-2,4-bis(4-chlorobenzylidene)-5-oxo-1-phenylpyrrolidine-3-carboxylic acid (BCOPCA)

Abstract: The synthesized compound (2Z,4Z)-2,4-bis(4-chlorobenzylidene)-5-oxo-1-phenylpyrrolidine-3-carboxylic acid (BCOPCA) was characterised by Ultraviolet, FT-Infra Red, 1H, 13C Nuclear Magnetic Resonance and mass spectroscopy. The compound was further subjected to quantum chemical calculations at the level of density functional theory (DFT) using 6-31G (d,p) basis sets method with B3LYP and CAM-B3LYP hybrid functionals. The intramolecular interactions, polarizability, hyperpolarizability and nonlinear optical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Red colour displays nucleophilic area while blue displays electrophilic area [35, 36, 37, 38]. The yellow, green and light blue colours characterized somewhat electron rich; neutral and somewhat electron defective areas, respectively [39, 40]. It can be seen that oxygen atoms in C=O and C–O bonds have maximum negative electrostatic potential due to their considerable intrinsic electronegative characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…Red colour displays nucleophilic area while blue displays electrophilic area [35, 36, 37, 38]. The yellow, green and light blue colours characterized somewhat electron rich; neutral and somewhat electron defective areas, respectively [39, 40]. It can be seen that oxygen atoms in C=O and C–O bonds have maximum negative electrostatic potential due to their considerable intrinsic electronegative characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…Related to C=O bands, two carbonyl groups are presented: C=O for the carbonyl of the acid moiety, which is displayed at 1738 cm −1 for 3a and 1730 cm −1 for 3b as medium bands. In this sense, Devi et al [59] detected this band at 1766 cm −1 ; Devi et al [60] reported this band at 1729 cm −1 . For C=O, the carbonyl of the ketone moiety is displayed as medium bands at 1621 cm −1 for 3a and 1617 cm −1 for 3b; this band is easily to identify due to higher strength and conjugation with the double bonds C5=C6 or C3=C4.…”
Section: Experimental and Theoretical Vibrational Spectramentioning
confidence: 93%
“…These values are according to those reported by Devi et al [59] at 3634 cm −1 using the B3LYP method with a 6-31G(d,p) basis set. Also, Devi et al [60] reported the value for OH at 3545 cm −1 .…”
Section: Experimental and Theoretical Vibrational Spectramentioning
confidence: 96%